Dysfunctional tribalism in Ernest Hemingway's The Sun Also Rises. Issue 1 (16th February 2021) - Liu, Meichen Paris
Abstract: This paper explores the cliquish behavior of the group of friends and acquaintances in Ernest Hemingway's The Sun Also Rises, arguing that sexual dysfunction is portrayed as part of a larger malaise of dysfunctional tribalism which affects social dynamics in the modern world.